1918
DOI: 10.1002/ange.19180313904
|View full text |Cite
|
Sign up to set email alerts
|

Über die Natur der Cellulose aus Getreidestroh

Abstract: Dentaohbnd und den n6rdliohen wie W h e n Gebiotun Knlllandr mit EirlschluB Sibiriena emcheinen. Riga ist eomit mch der 01%. .PO die dcuteche Rirtechaft Mnftig einen guten Teil jener hochd i g e n Waren hcrstellcn a4rd, dnrch welohen sie ihre beaondere Stellung auf dcm Weltmarkt einnimmt. Welche maligebende Be-~ deutnng a k r cine wuwnschdtlich-hhnisobe hhrtmatalt, gleichsam ein Nervenzentrum dea Wirtachaftaktirpem fiir einc solche Entwioklung hat. braucht in I)euteohlend nicht erst paohgcwiesou su werden. Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1918
1918
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, non-detoxi®ed lignocellulosic hydrolysate contains substances that act as electron acceptors that regenerate NAD + . Furfural and HMF, which are formed by thermal degradation of pentoses (Antal et al, 1991;Dunlop, 1948) and hexoses (Antal et al, 1990;Heuser and Schott, 1923), respectively, are the two most common aldehydes (Larsson et al, 1999). These substances inhibit ethanolic glucose fermentation by causing longer lag phase (Taherzadeh et al, 2000a;Sanchez and Bautista, 1988) and lower growth rate (Boyer et al, 1992;Palmqvist et al, 1999b;Sanchez and Bautista, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, non-detoxi®ed lignocellulosic hydrolysate contains substances that act as electron acceptors that regenerate NAD + . Furfural and HMF, which are formed by thermal degradation of pentoses (Antal et al, 1991;Dunlop, 1948) and hexoses (Antal et al, 1990;Heuser and Schott, 1923), respectively, are the two most common aldehydes (Larsson et al, 1999). These substances inhibit ethanolic glucose fermentation by causing longer lag phase (Taherzadeh et al, 2000a;Sanchez and Bautista, 1988) and lower growth rate (Boyer et al, 1992;Palmqvist et al, 1999b;Sanchez and Bautista, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Aldehydes and ketones such as acetaldehyde, acetoin, and acetone have been reduced to ethanol, butanediol, and 2-propanol, respectively, under simultaneous conversion of NADH to NAD + and concomitant decrease in xylitol excretion. Lignocellulosic hydrolysates contain aldehydes, and the most common non-aromatic ones are furfural and 5-hydroxymethylfurfural (HMF) (Heuser and Schott, 1923;Larsson et al, 1999). Furfural and HMF are reduced to furfuryl alcohol and 5-hydroxymethylfurfuryl alcohol (HMFAL), respectively, during yeast fermentation (Nemirovskii et al, 1989;Palmqvist et al, 1999a;Taherzadeh et al, 2000a;Villa et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical behaviour of these furfurol-yielding bodies also shows their resistibility. Heuser and Haug (14) found that treatment with boiling 6 per cent. caustic soda did not reduce the xylan content of straw below 9.7 per cent.…”
Section: The Figures Inmentioning
confidence: 99%